Menu Engineering on Main Course to Increase Sales - Ni Kadek Ayu Saraswati; Ni Ketut Bagiastuti; Ida Ayu Elistyawati; Made Sudiarta (International Journal of Glocal Tourism, 2020)
Purpose: This research is to determine the level of popularity and the level of contribution margins on the main course menu and strategies that can be done to increase food sales at a restaurant of a big hotel located in Kuta, Bali, Indonesia. Research methods: The method used in this research is observation, interviews, literature study, and documentation. The data analysis technique used is the menu engineering analysis technique. Findings: Among 18 main course menus, 3 or 16.7% is categorized into the high popularity level and 15 or 83.3% into the low popularity level. Fourteen menus or 77.8% have a high contribution margin level is and the menu that has a low contribution margin level is 4 menus or 22.2%. There are 3 menus or 16.7% in the plowhorse category, as many as 14 menus or 77.8% into the puzzle category, and there are 1 menu or 5% into the dog category. Implication: Strategies to increase food sales are by maintaining the menu, maintaining quality and increasing food prices, promoting the menu, and considering deleting the menu or replacing it with a new menu.